The Relationship between Occupational Exposure to Lead and Hearing Loss in a Cross-Sectional Survey of Iranian Workers - Ghiasvand, Masoumeh; Mohammadi, Saber; Roth, Brett; Ranjbar, Mostafa (Frontiers in Public Health, 2016)
Objectives: Ototoxic effect of exposure to lead has been reported by many researchers to be leading to deafness. This study was undertaken with a view to evaluate the effects of occupational lead exposure on hearing loss in workers in a lead-acid battery manufacturing plant in Tehran, Iran. Methods: In a cross sectional study, 609 male workers were recruited from different locations in the factory. Association between blood lead level (BLL) and hearing loss in different frequencies were measured. Logistic regression analysis was used to measure the relationship between exposure to lead and hearing loss. Statistical significance was defined as P-value < 0.05. Results: Out of the 609 male workers evaluated, 285 (46.8%) had BLL < 40µg/dl and 324 (53.2%) had BLL > 40 µg/dl. Mean noise exposure level was 80 dB. High frequency hearing loss (3, 4, 6 and 8 KHz) above 25 db in either ear was significantly more prevalent in workers with BLL > 40 µg/dl (Adjusted Odds Ratio =2.66, 95% CI:1.86 -3080, p<0.001 and Adjusted Odds ratio = 1.60, 95% CI: 1.13-2.27, p<0.008 for age and work duration respectively). Conclusion: Health surveillance program should include conservation of hearing program in workers exposed to lead even if the ambient noise level is less than of time weighted average of 85 db A. Periodic Hearing assessment by pure tone audiometry is recommended since it is a relatively simple procedure to identify hearing loss. An early detection will help in prevention of permanent hearing loss.